Associations of Bone Mineral Density and Lead Levels in Blood, Tibia, and Patella in Urban-Dwelling Women - Theppeang, Keson (National Institute of Environmental Health Sciences, 2008)
OBJECTIVE: The objective of this study was to evaluate the relations between bone mineral density (BMD) and lead in blood, tibia, and patella and to investigate how BMD modifies these lead biomarkers in older women. DESIGN: In this study, we used cross-sectional analysis. PARTICIPANTS: We studied 112 women, 50–70 years of age, including both whites and African Americans, residing in Baltimore, Maryland. MEASUREMENTS: We measured lumbar spine BMD, blood and bone lead by dual energy X-ray absorptiometry, anodic stripping voltammetry, and (109)Cd-induced K-shell X-ray fluorescence, respectively. We measured vitamin D receptor and apolipoprotein E (APOE) genotypes using standard methods. RESULTS: Mean (± SD) BMD and lead levels in blood, tibia, and patella were 1.02 ± 0.16 g/cm(2), 3.3 ± 2.2 μg/dL, 19.7 ± 13.2 μg/g, and 5.7 ± 15.3 μg/g, respectively. In adjusted analysis, higher BMD was associated with higher tibia lead levels (p = 0.03). BMD was not associated with lead levels in blood or patella. There was evidence of significant effect modification by BMD on relations of physical activity with blood lead levels and by APOE genotype on relations of BMD with tibia lead levels. There was no evidence that BMD modified relations between tibia lead or patella lead and blood lead levels. CONCLUSIONS: We believe that BMD represents the capacity of bone that can store lead, by substitution for calcium, and thus the findings may have relevance for effect-size estimates in persons with higher BMD. RELEVANCE TO CLINICAL PRACTICE: The results have implications for changes in lead kinetics with aging, and thus the related risk of health effects associated with substantial early- and midlife lead exposure in older persons.